Association between body mass index and chronic obstructive pulmonary disease in young individuals: a nationwide population‑based cohort study - Chiwook Chung; Hajeong Kim; Kyu Na Lee; Dong Wook Shin; Sei Won Lee; Kyungdo Han (Scientific Reports)
Abstract Body mass index (BMI) is associated with chronic obstructive pulmonary disease (COPD) risk. We investigated the association between BMI and the risk of COPD among young individuals. Using the Korean National Health Information Database, we screened individuals aged 20–39 years who participated in the national health examination between 2009 and 2012. We identified 6,304,769 eligible individuals, and 13,784 had newly developed COPD. BMI was categorized according to the Asian BMI criteria. We performed multivariate Cox proportional hazards models to estimate the adjusted hazard ratio (aHR) of risk factors for COPD development. Their mean age was 30.8 ± 5.0 years, and 3,732,656 (59.2%) were men. The incidence rate for developing COPD was 0.22/1,000 person-years. Compared to individuals with normal BMI (18.5–22.9 kg/m2), those who were underweight (< 18.5 kg/m2) had higher risks of COPD development (aHR: 1.37, 95% confidence interval [CI]: 1.29–1.46). Meanwhile, overweight or obese individuals (23–24.9 or 25–29.9 kg/m2) had lower risks for COPD development (aHR 0.90, 95% CI 0.86–0.95, and aHR 0.90, 95% CI 0.85–0.94, respectively). Although males showed tendencies similar to those of the total population, the risk was increased with increasing BMI among females. In the subgroup analysis, the risk reduction was not observed among non-smokers as BMI increased. In young individuals, being underweight was associated with an increased risk for COPD development, whereas being overweight and obese were associated with a decreased risk for COPD.